The dilemma of electronic books in the mobile age in Taiwan - Kuo-feng Tseng (International Telecommunications Society (ITS), 2013)
As the voice profits of the mobile phone companies continuously decline in Taiwan, they need to find other revenues from the digital contents to survive in the mobile age. The mobile phone companies had created several online platforms to sell digital video, music and books. Especially in the past two years, as more and more customers had the big screens of portable tablet PC or smart phones, the sale of the e-books becomes the major marketing strategy to promote the penetration of smart phones in Taiwan. However, few e-books were available in the mobile online platforms in the past few years, so this study conducted the survey of the book publishing industry to understand the major factors. The results show: first, few copyrights of the popular oversea books are available; second, only the book conglomerate are willing to take the risk to launch the e-book services; third, currently the sales of the e-books are not able to compensate the costs; fourth, there is no such a platform to let all kind of e-books available in Taiwan.
Keywords: 330; e-book; digital book; business model; industry survey; mobile device